ANATOMY EDUCATION IN CAMPUS FLORESTA, UNIVERSIDADE FEDERAL DO ACRE: THE USE OF ANIMAL SKELETONS AS DIDACTIC RESOURCESENSINO DE ANATOMIA NO CAMPUS FLORESTA, UNIVERSIDADE FEDERAL DO ACRE: O USO DE ESQUELETOS ANIMAIS COMO RECURSOS DIDÁTICOS - Jacó, Tiago Ricardo Fernandes; Leite, Antonio Tarlei de Souza; Casas, André Luis da Silva (South American Journal of Basic Education, Technical and Technological, 2018)
The study of anatomy, since the beginning of the formation of western culture, was derived from philosophical and methodological basis for understanding the form, function and origin of the man. It has been the basis for students of the courses in Health Sciences and Biological Sciences, with indispensable use of corpses and/or cadaveric parts for a better understanding of the structures of the human body and animals. Thus, using mainly techniques of biological maceration and necrophagous insects (Coleoptera, Dermestes maculatus), it was possible to prepare 13 complete skeletons of animals that are being used in the disciplines of Human and Animal Anatomy taught at the Didactic Laboratory of Comparative Anatomy and Physiology of the Universidade Federal do Acre, Campus Floresta, Brazil. O estudo da Anatomia desde o inicio da formação da cultura ocidental, baseou-se em bases filosóficas e metodológicas para entender a forma, a função e a origem do homem. Tem sido a base para estudantes dos cursos de Ciências da Saúde e Ciências Biológicas, com a indispensável utilização de corpos e/ou partes cadavéricas para uma melhor compreensão das estruturas dos corpos dos animais e dos seres humanos. Assim, utilizando técnicas de maceração biológica e insetos necrófagos (Coleoptera, Dermestes maculatus), foi possível preparar 13 esqueletos completos de animais que tem sido utilizado nas disciplinas de Anatomia humana e animal ministradas no Laboratório Didático de Anatomia e Fisiologia Comparada da Universidade Federal do Acre, Campus Floresta, Brasil.